Complex Regional Pain Syndrome of Non-hemiplegic Upper Limb in a Stroke Patient: A Case Report - Ahry Lee; Youjin Jung; Hee-Kyu Kwon; Sung-Bom Pyun (Annals of Rehabilitation Medicine, 2018)
Complex regional pain syndrome (CRPS) type I in stroke patients is usually known to affect the hemiplegic upper limb. We report a case of CRPS presented in an ipsilesional arm of a 72-year-old female patient after an ischemic stroke at the left middle cerebral artery territory. Clinical signs such as painful range of motion and hyperalgesia of her left upper extremity, swollen left hand, and dystonic posture were suggestive of CRPS. A three-phase bone scintigraphy showed increased uptake in all phases in the ipsilesional arm. Diffusion tensor tractography showed significantly decreased fiber numbers of the corticospinal tract and the spinothalamic tract in both unaffected and affected hemispheres. Pain and range of motion of the left arm of the patient improved after oral steroids with a starting dose of 50 mg/day.